Porównanie jakości i organizacji zajęć prowadzonych w ramach AZS wśród wybranych uczelni Górnego Śląska = Comparison of quality and organization of physical activities organized by University Sports Association at selected universities of the Upper Silesia - Dyla, Michalina; Rżany, Michał; Rzadkowska, Aleksandra; Suszyński, Krzysztof; Górka, Dariusz (Journal of Education, Health and Sport, 2015)
Dyla Michalina, Rżany Michał, Rzadkowska Aleksandra, Suszyński Krzysztof, Górka Dariusz. Porównanie jakości i organizacji zajęć prowadzonych w ramach AZS wśród wybranych uczelni Górnego Śląska = Comparison of quality and organization of physical activities organized by University Sports Association at selected universities of the Upper Silesia. Journal of Education, Health and Sport. 2015;5(11):606-615. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35710 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A606-615 http://pbn.nauka.gov.pl/works/684918 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Dyla Michalina, Rżany Michał, Rzadkowska Aleksandra, Suszyński Krzysztof, Górka Dariusz. Porównanie jakości i organizacji zajęć prowadzonych w ramach AZS wśród wybranych uczelni Górnego Śląska. Quality in Sport. 2015;1(3):28-37. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Michalina Dyla1, Michał Rżany2, Aleksandra Rzadkowska1, Krzysztof Suszyński2, Dariusz Górka2 1 Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach, Studenckie Koło Naukowe przy Zakładzie Medycyny Sportowej i Fizjologii Wysiłku Fizycznego Katedra Fizjoterapii 2Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach, Katedra Fizjoterapii, Zakład Medycyny Sportowej i Fizjologii Wysiłku Fizycznego Porównanie jakości i organizacji zajęć prowadzonych w ramach AZS wśród wybranych uczelni Górnego Śląska Comparison of quality and organization of physical activities organized by University Sports Association at selected universities of the Upper Silesia Streszczenie Wstęp. W ostatnich latach coraz większym zainteresowaniem cieszą się zajęcia organizowane na siłowniach, dlatego właśnie one, prowadzone w ramach zajęć Akademickiego Związku Sportowego, są coraz częściej wybierane przez wielu studentów. Jednak, aby ćwiczenia przynosiły pożądany efekt, muszą być wykonywane poprawnie. Stosowanie zbyt dużego obciążenia, liczby powtórzeń lub złej techniki może być przyczyną urazu lub kontuzji, czego następstwem może być poważny uszczerbek na zdrowiu. Celem pracy było sprawdzenie jakości i organizacji zajęć prowadzonych w ramach AZS wśród wybranych uczelni Górnego Śląska. Postanowiono zbadać: Czy istnieje zależność pomiędzy rodzajem uczelni a kontrolą zdrowia osób zaczynających zajęcia na siłowni? Czy typ uczelni ma wpływ na przykładanie się studentów do poprawnego wykonywania ćwiczeń na siłowni? Czy istnieje zależność pomiędzy rodzajem uczelni a długością treningu siłowego? Materiał i metodyka. Zbadano 120 osób w tym 44 kobiety w wieku od 17 do 24 lat (x=20,8;SD= 1,8) oraz 76 mężczyzn w wieku od 17 do 28 lat (x=21,8; SD= 1,9). Byli to studenci z następujących górnośląskich uczelni wyższych: ŚUM, AWF, UŚ oraz UE, którzy regularnie uczęszczają na siłownie w ramach AZS. Zastosowano autorską ankietę. Pytania dotyczyły uczestnictwa w zajęciach na siłowni, doboru ćwiczeń w kontekście możliwości zdrowotnych studentów, prezentacji poprawnej techniki wykonywanych ćwiczeń, informacji o synchronizacji ćwiczeń z oddechem oraz kontroli poprawności techniki studentów bez ich prośby o nią. Analiza statystyczna została wykonana za pomocą programu Statistica. Wyniki. Analiza wariancji ANOVA wykazała istotnie statystycznie zależność pomiędzy rodzajem uczelni a kontrolą stanu zdrowia osób rozpoczynających zajęcia na siłowni (p=0,005). Najczęściej zdrowie tych osób jest kontrolowane na ŚUM w Katowicach. Brak jest zależności pomiędzy typem uczelni a przykładaniem się do poprawności wykonywanych ćwiczeń podczas zajęć na siłowni (p=0,35). Długość treningu siłowego nie zależy od rodzaju uczelni. Najwięcej czasu na siłowni spędzają studenci AWF w Katowicach a najmniej studenci ŚUM w Katowicach. Wnioski. Częstość kontroli stanu zdrowia osób rozpoczynających zajęcia na siłowni jest zależna od rodzaju uczelni. Rodzaj uczelni nie ma związku z przykładaniem się do poprawności ćwiczeń siłowych Długość treningu na siłowni nie zależy od rodzaju uczelni. Słowa kluczowe: jakość, poprawność, uraz, kontrola, siłownia, ćwiczenia. Abstract Introduction. Gym exercises have become more and more popular in the recent years. Thus, it is not surprising that this form of physical activity offered by University Sports Association has become a popular choice among the university students. However, to benefit from the workout, the exercises must be performed correctly. Application of excessive loads, number of repetitions, or poor technique can cause injury, which may lead to serious physical damage. Aim. The aims were to check the quality and organization of physical activities ogranized by University Sports Association in chosen universities of the Upper Silesia. The questions asked were: 1. Is there a correlation between different universities and the health control among new students at the gym? 2. Does the type of university correlate with the quality of the workout? 3. Is there a correlation between the type of university and the duration of the strength training? Materials and Methods. 120 students were examined, among which there were 44 women aged 17 to 24 (x=20,8;SD= 1,8) and 76 man aged 17 to 28 (x=21,8; SD= 1,9). They were university students from the following Upper Silesian universities: ŚUM, AWF, UŚ and UE, who regularly practise gym exercises organized by Academic Sports Association. An original questionnaire was created for the purpose of this study. The questions concerned participation in the gym activities, choice of exercises in context of their health predispositions, presentation of the proper technique of exercises, information about synchronization exercises with breath and quality control of performed exercises without prior request of the students. Statistical analysis was performed by a program Statistica. Results. Analysis of variance (ANOVA) demonstrated a statistically significant relation between the type of university and the health control among new students at the gym (p=0,005). ŚUM is the university where the students are the most often controlled. There is no correlation between the type of university and the quality of the training (p=0,35). The duration of strength training is not correlated with the type of university. Students of AWF Katowice spend the most time at the gym, whereas students from ŚUM Katowice spend the least. Conclusion 1. Frequency of the health control among students starting classes at the gym depends on the type of university. 2. The type of university does not affect the quality of the training. 3. The duration of training does not depend on the type of university. Key words: quality, injury, control, gym, exercises.